SOIL–SOIL SOLUTION DISTRIBUTION COEFFICIENT OF RADIOIODINE IN SURFACE SOILS AROUND SPENT NUCLEAR FUEL REPROCESSING PLANT IN ROKKASHO, JAPAN. Issue 13 (9th September 2022) - Takeda, Akira; Unno, Yusuke; Tsukada, Hirofumi; Takaku, Yuichi; Hisamatsu, Shunichi
Abstract: The soil-soil solution distribution coefficient (Kd ) of radioiodine in soil samples with various total carbon (TC) contents was measured in a batch sorption experiment using 125 I tracer spiked as I − . The log values of Kd− 125 I and TC concentration in low-TC soils (< 10g kg −1 ) were positively correlated, whereas those of Kd− 125 I in TC rich soils (> 10 g kg −1 ) and dissolved organic carbon (DOC) in liquid phase were negatively correlated. The proportion of 125 I in the < 3 kDa fraction in the liquid phase is negatively correlated with the log of DOC, implying that 125 I is primarily combined with high-molecular-weight organic matter in soil solutions rich in DOC. The results suggest that Kd− 125 I in soil with high soil organic material (SOM) content is governed by DOC via the combination of 125 I and DOC. In contrast, Kd− 125 I in soils with a low SOM content was governed by SOM because the anion exchange capacity of SOM was vital for the sorption of 125 I − .